2011
DOI: 10.1186/1745-6215-12-216
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness evaluation of an integrated automatic termomechanic massage system (SMATH® system) in non-specific sub-acute and chronic low back pain - a randomized double-blinded controlled trial, comparing SMATH therapy versus sham therapy: study protocol for a randomized controlled trial

Abstract: BackgroundLow back pain (LBP) is a major health problem in modern society, with 70-85% of the population experiencing LBP at some time in their lives. Each year, 5-10% of the workforce misses work due to LBP, most for less than 7 days. Almost 10% of all patients are at risk of developing chronic pain and disability. Little clinical evidence is available for the majority of treatments used in LBP therapy. However, moderate evidence exists for interdisciplinary rehabilitation, exercise, acupuncture, spinal manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…On the other hand, the acupressure group of the present study showed more improvement in the pain component of the WOMAC scale. This is in congruence with previous studies that demonstrated the effectiveness of this treatment modality in the relief of various types of pain such as low back pain [44] , dysmenorrhea [45] , and pain in breast cancer [46] . The pain relief of acupressure has been attributed to its analgesic action, which has been considered by Litscher [21] as similar to general anesthesia.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the acupressure group of the present study showed more improvement in the pain component of the WOMAC scale. This is in congruence with previous studies that demonstrated the effectiveness of this treatment modality in the relief of various types of pain such as low back pain [44] , dysmenorrhea [45] , and pain in breast cancer [46] . The pain relief of acupressure has been attributed to its analgesic action, which has been considered by Litscher [21] as similar to general anesthesia.…”
Section: Discussionsupporting
confidence: 91%
“…Preference is given to conservative non-pharmacological treatments [9], with a wide range of recommendations. There are more than 50 different potential therapies promising pain relief or even healing, but only few have been thoroughly evaluated by evidence-based methods [10]. For patients already suffering from back pain, recurrences and chronification can be prevented best by multimodal programs, which means the combination of different sorts of therapy [11].…”
Section: Introductionmentioning
confidence: 99%
“…Massage therapy has been shown to a ect both structure and function of the musculoskeletal system by promoting a relaxation response, decreasing muscle tension, and decreasing tonic muscle contractions [13][14][15][16]. In recent years, the integration of mechanical instruments to support the implementation of massage therapies such as massage chairs [5][6][7], automatic massage systems [6], or robotic systems [17][18][19][20][21] has bene ted therapists and their patients.…”
Section: Related Workmentioning
confidence: 99%
“…ere also exist automatic massage systems such as medical devices that combine basic principles of mechanical massage, thermotherapy, acupressure, infrared therapy, and moxibustion. For instance, the device described in [6] is capable of releasing modulated and controlled thermomechanical energy on the patient following a programmable and fully reproducible automatic treatment program selected by the operator. Another example of automatic massage systems is robotic systems that use massage patterns, for example, robots that provide maxillofacial massages [17], massage of the back [20,21,25], or feet massage [18].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation